After All This Time, Isn't It Still 'About Time'? Artist's Work in Slide-Tape in the UK Since the 1970s. Issue 1 (19th December 2019) - White, Mary C.
Abstract : This article will address the use of slide-tape by artists during the 1970s and 1980s in the United Kingdom. Slide-tape is seen now as a form that was abandoned and barely worthy of mention by critics and historians, and so has been largely elided in the literature. However, it is significant in the UK for being used by a number of key and emerging artists during the period, where it became a distinctive approach to using image and sound. The aesthetic qualities of slide-tape and the physical presence of media apparatus were exploited in both its performance and installation by a range of artists who are associated with experimental approaches to time-based media. It was also developed as a critical tool by women artists and black artists, and this too is overlooked and that moment forgotten. Overall, artists work in this form has been ignored. I speculate on the reasons why this has happened, having recounted some key points in its development and make an argument for its contribution to artists' moving image media, whose histories are still being written.